2023
DOI: 10.30596/ijbe.v5i1.16161
|View full text |Cite
|
Sign up to set email alerts
|

The role of Institutional quality, human capital development on economic growth in Sub-Saharan Africa

Abstract: Purpose -The paper examined the role of institutional quality and human capital development on economic growth in Sub-Saharan African (47) countries. Methodology -The study employed secondary data from all the countries within the Sub-Saharan African countries region for the period of nineteen years, with the exclusion of South Sudan due to insufficient data; all the data was sourced from the World Bank Database and was analyzed via the use of fixed effects regression based on the nature of the study (i.e., Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
(102 reference statements)
1
0
0
Order By: Relevance
“…It also demonstrates that a decrease in the number of years since the most recent regime change or the conclusion of a transition period leads to reduced corruption and subsequently diminishes capital flight. This finding is consistent with the empirical results obtained by [ 82 ], who observed that more extended regime durability is linked to increased capital flight due to weaker governance, heightened corruption, and a less favorable domestic investment climate. Thus, it becomes evident that regime durability plays a crucial role in elucidating the impact of corruption on capital flight.…”
Section: Resultssupporting
confidence: 93%
“…It also demonstrates that a decrease in the number of years since the most recent regime change or the conclusion of a transition period leads to reduced corruption and subsequently diminishes capital flight. This finding is consistent with the empirical results obtained by [ 82 ], who observed that more extended regime durability is linked to increased capital flight due to weaker governance, heightened corruption, and a less favorable domestic investment climate. Thus, it becomes evident that regime durability plays a crucial role in elucidating the impact of corruption on capital flight.…”
Section: Resultssupporting
confidence: 93%